Biodiversity of Decapoda in Guinea-Bissau waters - Jesús, Nair de; Matos-Pita, Susana Soto de; Ramil, Francisco; Ramos, Ana (2016)
Two multidisciplinary surveys aimed to evaluate demersal and pelagic resources were conducted in the framework of the CCLME-FAO project in Northwest African region between October to December 2011 and from May to July 2012 on-board Norwegian R/V Dr. Fridtjof Nansen. A total of 580 stations were sampled with commercial trawl gear in the area spreading between the Gibraltar Strait and the Sierra Leone border. Fifty of these hauls were carried out in Guinea-Bissau waters between 48 and 983 meters depth. In both surveys, the research team of EcoAfrik project, belonging to the Spanish Institute of Oceanography and the University of Vigo, was responsible for the benthos sampling. At all stations the megabentic species, including decapod crustaceans, were sorted at morphospecies level and data of numerical abundance and biomass (wet weight) were collected. When the large volume of material did not allow the sampling of total catch, a subsample was worked, being after estimated the abundances and total biomass by a weighting factor. At every station living specimens of each species were protographed and a representative collection was preserved in 70% ethanol for further taxonomic study. The decapods collection taken in Guinea Bissau, composed by about 400 specimens, has been identified at the University of Vigo, and quantitative data have been analysed to stablish the distribution, composition and structure of the decapod communities. Abundance data (number of individuals) and weight (in kg) per station were standardized to a swept area of 0.1 km2 and matrices of numerical abundance and biomass by species and station were constructed to serve as basis for statistical analysis. Ecological descriptors, such as occurrence (O, presence of the species in the hauls), abundance (N), biomass (B), species richness (S), Shannon-Wiener diversity index (H') and Pielou equitability index (J') were estimated for each station. For the characterization of the assemblages, multivariate analysis (cluster and MDS) were applied to ...